2019
DOI: 10.1097/j.pain.0000000000001737
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in pronociceptive and antinociceptive mechanisms in patients with low back pain: a systematic review with meta-analysis

Abstract: Altered pro-nociceptive and anti-nociceptive mechanisms are often implicated in painful conditions and have been increasingly studied over the past decade. For some painful conditions alterations are well-established, but in low back pain (LBP) populations there remains considerable debate whether these mechanisms are altered. The present systematic review aimed to address this issue by identifying studies assessing Conditioned Pain Modulation (CPM) and/or Temporal Summation of Pain (TSP) in LBP patients, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 87 publications
7
88
6
1
Order By: Relevance
“… 24 Also, Fingleton et al 40 observed reduced pressure pain thresholds (hyperalgesia) after both aerobic and isometric exercises in individuals with knee osteoarthritis who demonstrated an impaired CPM response. By contrast, pain thresholds increased in knee osteoarthritis individuals with a normal CPM response suggesting that patients with impaired CPM, which is also a common finding in individuals with chronic pain, 114 , 121 may have less acute hypoalgesic effect from exercise.…”
Section: Pain Outcomes After Acute and Regular Exercise In Individmentioning
confidence: 91%
See 1 more Smart Citation
“… 24 Also, Fingleton et al 40 observed reduced pressure pain thresholds (hyperalgesia) after both aerobic and isometric exercises in individuals with knee osteoarthritis who demonstrated an impaired CPM response. By contrast, pain thresholds increased in knee osteoarthritis individuals with a normal CPM response suggesting that patients with impaired CPM, which is also a common finding in individuals with chronic pain, 114 , 121 may have less acute hypoalgesic effect from exercise.…”
Section: Pain Outcomes After Acute and Regular Exercise In Individmentioning
confidence: 91%
“…Individuals with facilitated central pain mechanisms, which are commonly observed in several chronic musculoskeletal pain conditions, 121 often report reduced hypoalgesia after exercise. Vaegter et al 197 observed reduced EIH after submaximal isometric exercise and after bicycling exercise in chronic pain patients with high widespread pain sensitivity compared with patients with low pain sensitivity.…”
Section: Pain Outcomes After Acute and Regular Exercise In Individmentioning
confidence: 99%
“…Conditioned pain modulation, which is considered a surrogate marker for central pain inhibition, has been extensively studied in many chronic pain syndromes including CLBP. 25 , 26 , 39 A recent meta-analysis evaluating CPM in patients with CLBP demonstrated reduced CPM responses in patients compared with controls. 26 This agrees with the results of this study where the majority of patients with CLBP (87%) showed aberrant CPM responses.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 31 , 39 Both a loss of pain inhibition and an increase in pain facilitation have been observed in patients with CLBP. 1 , 25 , 26 However, up to now, we remain uninformed on the association between the endogenous pain system and treatment efficacy in CLBP.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous attempts failed to show differences in SSp response profiles between healthy controls and chronic pain patients [16,19,47,49], which raised the question about the mechanism of SSp. Interestingly, previous studies in which other paradigms, also testing pain modulation, such as temporal summation [34], offset analgesia [51] or DNIC, showed distinct differences between chronic patients compared to healthy controls.…”
Section: Introductionmentioning
confidence: 91%